STUDI LITERATUR: FAKTOR PENDUKUNG PENERAPAN MODEL PROJECT BASED LEARNING PADA PEMBELAJARAN GAMBAR TEKNIK DI SMK - Anyjrah Narlita Isnaini (CV. ADIBA AISHA AMIRA, 2024)
This research aims to examine the factors that support the application of the Project Based Learning (PBJL) model in teaching Technical Drawing at Vocational High Schools (SMK). The background to this research is based on the importance of learning Technical Drawing in vocational schools and the challenges in its implementation, as well as the potential of the PBL model to improve the learning process. This research was carried out using the literature study method, where data was collected and analyzed from various sources such as journals, books and related articles. The research results revealed several main supporting factors in implementing the PBL model in teaching Engineering Drawing, such as teacher competence and understanding, student interest and motivation, availability of facilities and infrastructure, supporting curriculum and policies, as well as collaboration with industry. This research provides conclusions about important factors that need to be considered in implementing the PBJL model effectively and the implications of the findings for practitioners and further research.